Uppermost crustal structure regulates the flow of the Greenland Ice Sheet - Jones, G. A.; Ferreira, Ana M. G.; Kulessa, B.; Schimmel, Martin; Berbellini, A.; Morelli, A. (Nature Communications, 2021)
The flow of the Greenland Ice Sheet is controlled by subglacial processes and conditions that depend on the geological provenance and temperature of the crust beneath it, neither of which are adequately known. Here we present a seismic velocity model of the uppermost 5 km of the Greenlandic crust. We show that slow velocities in the upper crust tend to be associated with major outlet glaciers along the ice-sheet margin, and elevated geothermal heat flux along the Iceland hotspot track inland. Outlet glaciers particularly susceptible to basal slip over deformable subglacial sediments include Jakobshavn, Helheim and Kangerdlussuaq, while geothermal warming and softening of basal ice may affect the onset of faster ice flow at Petermann Glacier and the Northeast Greenland Ice Stream. Interactions with the solid earth therefore control the past, present and future dynamics of the Greenland Ice Sheet and must be adequately explored and implemented in ice sheet models. G.A.J. is funded through the by the Seȓ Cymru II Program in Low Carbon Energy and the Environment (European Regional Development Fund and Welsh European Funding Office; Project number 80761-SU-SU093). A.M.G.F. is grateful to support from NERC grant NE/N011791/1. M.S. thanks SANIMS (RTI2018-095594-B-I00). This project has received funding from the European Research Council (ERC) under the European Union’s Horizon 2020 research and innovation programme (grant agreement No 101001601). The seismic inversions presented in this study were carried out at UCL’s computer clusters Kathleen and Grace. Figures were generated using Matplotlib73. The Python toolbox obspyDMT74 was used to download the seismic data. Peer reviewed